Ecocentrism and criminal justice. (August 2018) - White, Rob
Ecocentrism refers to valuing nature for its own sake. This ecophilosophical orientation requires that all social practices incorporate ecological sensitivities and heightened awareness of the intrinsic value of non-human entities. This article explores what ecocentrism means for criminal justice and how the core principles of an ecocentric worldview translate into concrete application. Trends within criminal justice that are broadly supportive or reflective of ecocentrism are summarized. The article also considers the limitations of ecocentrism, particularly in the context of criminal law and in regards to the prosecution of human subjects for environmental offences. A basic premise of the article is that for those interested in eco-justice and green criminology, it is vitally important to describe what an eco-just future might look like, and this includes recognition of and support for already existing ecocentric initiatives evident in some policies and practices across criminal justice institutions.